The Study of Visitors’ Satisfaction at Gunung Kidul Regency Tourist Destinations: An Application of Holiday Satisfaction (HOLSAT) Model - Popi Irawan (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2017)
This study focuses its analysis on tourist satisfactions in various tourist destinations in the area of Gunung Kidul Regency of Yogyakarta Special Region. Analysis on tourist satisfaction in this research utilizes the Holiday Satisfaction (HOLSAT) model, first proposed by Tribe and Snaith. Its primary principle in evaluating tourist satisfactions is determined by comparing tourist perceptions on their holiday activities prior to doing activities (expectation) and after (experience) they do the activities. Survey is the primary research method applied in this study, in which questionnaire is designed based on the HOLSAT model itself. Analyses reveal that as a new, developing tourist destination in Yogyakarta, the tourist holiday satisfaction level in various tourist attractions in the area of Gunungkidul Regency is notably high for attraction attributes. The average mean of expectation and experience using the HOLSAT model in this research shows that attributes categorized as attraction and activities components are those that are highly perceived by the respondents. This means that in these two elements the tourists are satisfied. On the other hand, attributes categorized in accessibilities and amenities components receive the least score by the respondents, which means that the tourist are not satisfied in these items.